JJ Mak Pon Muar / Nur Farhana Abdul Aziz, Nor Ayu Othman, Nurul Ain Abd Rahman, Nur Najaa Najlaa' Bakar and Nurul Nabihah Mohammad Pauzan - Abdul Aziz, Nur Farhana; Othman, Nor Ayu; Abd Rahman, Nurul Ain; Bakar, Nur Najaa Najlaa'; Mohammad Pauzan, Nurul Nabihah (2019)
To learn deeper about the business environment, a case study is one of the best ways to do. In our case study, we focused on food industries because it is a continuous and the most opportunity came from this industry itself. Our team members conduct interview in Jalan Junid, Muar with the entrepreneur under Small Medium Enterprise (SME). Based on the interview. we managed to discover the business problem.